Particulate matter and hospital admissions due to ischemic heart disease in Sorocaba, SP - Samara da Silva Gavinier; Luiz Fernando C. Nascimento (Revista Ambiente & Água, 2013)
There is evidence that air pollution is a risk factor for ischemic heart diseases (IHD). The objective of this study was to estimate the association between exposure to particulate matter (PM10) and hospital admissions due to ischemic heart diseases. It was a time-series ecological study with individuals of both genders, 50 or more years old, and residents of Sorocaba, São Paulo. The admission data was obtained from the DATASUS site according to ICD-10 (I20 to I22 and I24 to I25.0), for the period from January 1st 2007 to December 31st 2010. The concentrations of air pollutants (particulate matter, ozone, nitrogen dioxide, nitrogen oxide and oxides of nitrogen), temperature and mean relative humidity were provided by the São Paulo State Environmental Agency. The generalized additive model Poisson regression with lags of up to four days was used. There were 1804 admissions during the period. Exposure to PM10 was significantly associated with hospitalization for IHD two and four days after exposure with RR = 1.006, 95% CI 1.001-1.012 and an increment of 21 μg m-³ was associated with an increase of 13% in risk of hospitalization two days after exposure and 14% after four days. It was therefore possible to identify an association with exposure to PM10 in hospitalizations due to ischemic heart diseases in individuals from a medium-sized city of Sao Paulo.